1999
DOI: 10.1021/ac990205u
|View full text |Cite
|
Sign up to set email alerts
|

A Calixarene-Based Fluorogenic Reagent for Selective Mercury(II) Recognition

Abstract: The first calixarene-based fluorogenic Hg(II)-selective extractant, 5,11,17,23-tetrakis(1,1-dimethylethyl)-25,27-bis(N-(5-dimethylaminonaphthalene-1-sulfonyl)carbamoylmethoxy)-26,28-dimethoxycalix[4]arene (2), is reported. In solvent extraction from aqueous acidic solutions (HNO(3)), 2 exhibits excellent selectivity for Hg(II) over a wide range of transition, alkali, and alkaline earth metal cations. Quenching of its fluorescence due to Hg(II) coordination is unaffected by the presence of 100-fold excesses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 11 publications
(15 reference statements)
1
59
1
Order By: Relevance
“…From N-(X)sulfonyl carboxamide derivatized calix [4]-arene, which is selective for Hg 2+ in extraction [177] the fluorophore 37 was derived, the 520 nm emission of which is quenched upon complexation due to electron transfer [178]. Utilizing the cation-π-interaction of the phenyl rings, Tl + could be selectively sensed by the propyl ether of de-t-butylated calix [4]arene in an ISE with log K Tl,M = -1.35 (Ag), -2.7 (Hg), <-4.0 (K, NH 4 , H, Pb), <-5 (Ca, Na, Mg), lin.…”
Section: Other Heavy Metal Ion Recognitionmentioning
confidence: 99%
“…From N-(X)sulfonyl carboxamide derivatized calix [4]-arene, which is selective for Hg 2+ in extraction [177] the fluorophore 37 was derived, the 520 nm emission of which is quenched upon complexation due to electron transfer [178]. Utilizing the cation-π-interaction of the phenyl rings, Tl + could be selectively sensed by the propyl ether of de-t-butylated calix [4]arene in an ISE with log K Tl,M = -1.35 (Ag), -2.7 (Hg), <-4.0 (K, NH 4 , H, Pb), <-5 (Ca, Na, Mg), lin.…”
Section: Other Heavy Metal Ion Recognitionmentioning
confidence: 99%
“…Bartsch and co-workers showed that a calix [4]arene bearing N(X)sulfonylcarboxamide exhibits a good extraction selectivity for Hg 2 + and Pb 2 + over alkali and transition-metal ions. [13] A calix [4]arene (2) with two dansyl groups as part of the N(X)sulfonylcarboxamide (Calix-DANS2) was used for selective Hg 2 + extraction in acidic solutions in the millimolar concentration range, [14] but no attention was paid to the possible detection of Hg 2 + at low concentration. In a preceding paper, we reported preliminary results on the synthesis and the photophysical properties of a new calixarene Calix-DANS4 (3) bearing four dansyl groups which has been designed for the sensitive and selective detection of Pb 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a wide variety of spectrophotometric methods for the determination of mercury have been reported. [9][10][11][12][13][14][15][16][17][18][19] Each chromogenic system has its advantages and disadvantages with respect to sensitivity, selectivity and analysis speed.…”
Section: Introductionmentioning
confidence: 99%